PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL MELALUI KOMITMEN ORGANISASI DAN MOTIVASI - Ernis, Frenni; Sularso, Raden Andi; Wardayati, Siti Maria (BISMA: Jurnal Bisnis dan Manajemen, 2017)
Abstract: This study aimed to analyze the effect of budget participation on managerial performance with organizational commitment and motivation as the intervening variables. Data were collected by distributing questionnaires to structural officials of the Government of Bondowoso Regency. The collected data were then analyzed using Structural Equation Modeling (SEM). Results showed that budget participation has significant and positive effect on managerial performance. Budget participation also has a positive and significant effect on organizational commitment and motivation. Results of the research also demonstrate that organizational commitment and motivation have positive and significant effects on managerial performance. Budget participation also affects managerial performance through organizational commitment and motivation. Keywords: Budget Participation, Organizational Commitment, Motivation, Job Relevant Information, and Managerial Performance.